An Analysis of Figurative Language Used in Philip David Wickham’s Songs - Chaira Nurul Atiya; I Gde Agoes Caskara Surya Putra (Austronesian: Journal of Language Science & Literature, 2023)
The use of figurative language in Philip David Wickham’s songs can make the words sound lovely and intriguing. The aims of this research are to identify different kinds of figurative language and their interpretations in four songs from Philip David Wickham’s album “The Ascension”. The study employs a qualitative approach in order to provide a thorough description of the problems identified. The observation method was used in collecting the data. The researchers discovered sixteen pieces of data that contain figurative language in Philip David Wickham’s songs based on the discussion and analysis data, and there are four kinds of figurative language found in the song lyrics, such as simile, metaphor, personification, and hyperbole. Hyperbole is the most common form of figurative language in Philip David Wickham’s songs. The types of meaning used in song lyrics containing figurative language are connotative and conceptual meanings. These two types of meaning are the most widely used in interpreting the meaning of Philip David Wickham’s song lyrics.